Trust, Security and Privacy in Global Computing - Seigneur, Jean-Marc (University of Dublin, Trinity College, School of Computer Science and Statistics, 2005)
During the past thirty years, the world of computing has evolved from large centralised computing centres to an increasingly distributed computing environment, where computation and communication capabilities are being embedded in artefacts of everyday life. Billions of computational entities will interact in systems with ever changing configurations determined by local and global context, for example, the location of the user. In such dynamic environments, users would be overwhelmed if involved in computing-related decisions every time the context changes. Due to the number of decisions required to sustain continuous service, most decisions will have to be made by the computing entities themselves. Moreover, due to the global scale of the environment and the potential risk of disconnected operations, the computing entities may have to make these decisions autonomously, without relying on a given fixed infrastructure. Knowledge, especially about the context of the interaction, is vital for the accuracy of these decisions. However, keeping information on a global scale is unfeasible for resource-constrained entities, so some degree of uncertainty must be assumed.
Keywords: Computer Science